The genus Chionanthus (Oleaceae) in Cambodia, Laos and Vietnam - Quang, Bui Hong; Nuraliev, Maxim S. (Phytotaxa, 2021)
A synopsis of the genus Chionanthus is presented for Cambodia, Laos and Vietnam. Thirteen species, including four species endemic to the area, are recognized. Amongst them, twelve species, including two endemic species, are found in Vietnam, and nine and five species are recorded in Laos and Cambodia, respectively. Several species are reported as new records for Laos and Vietnam. Chionanthus verticillatus is reduced to a synonym of C. robinsonii. Lectotypes are designated for eight names currently treated within the genus Chionanthus. The type, synonyms, citations of relevant regional taxonomic publications, brief taxonomic notes, data on ecology, phenology and distribution and a list of all available specimens from the studied area are provided for each taxon. A key for identification of the species of Chionanthus in Cambodia, Laos and Vietnam is also presented.